Pedagogical blogging : promoting tertiary level students` critical thinking by using socratic questions. - Shahsavar, Zahra; Tan, Bee Hoon (National University of Singapore, 2013)
This study seeks to investigate the effects of pedagogical blogging on tertiary students’ critical thinking. The authors initially discuss the role of Socratic questions in promoting students’ critical thinking through Web 2.0 tools. They further explain how blogging was incorporated into the curriculum of a course for tertiary level students enrolled in a Malaysian university. Finally, they show how qualitative and quantitative methods were used to evaluate the efficiency of Socratic questions in students’ blogging and its effects on students’ critical thinking. Findings suggest that implementing Socratic questions in students’ blogging would help promote students’ critical thinking.